Analsis Pengaruh Profitabilitas, Leverage, Umur Listing, dan Ukuran Kap Terhadap Audit Report Lag (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2016-2018) - Indias Ilham Ramadhan Putra Muslim; Triyono Triyono (Neraca : Jurnal Akuntansi Terapan, 2021)
This study aims to exemine the effect of profitability, leverage, listing age, size of the public accounting firm on audit report lag in manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018. The Research sample used was 195 manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018. The sampling method uses purposive sampling method. The data used is secondary data. The analysis used in this study is multiple liner regression analysis processed using the Statistical Package for Social Science (SPSS) Version 21 program. The result showed that leverage and size of the public accounting firm variables affect the audit report lag while the variable profitability and listing age do not influence the audit report lag.